FAKTOR FAKTOR YANG BERHUBUNGAN DENGAN PRAKTIK CUCI TANGAN PAKAI SABUN PADA SISWA SD DI WILAYAH KERJA PUSKESMAS BANYUURIP PURWOREJO - Nurul Mukminah; VG Tinuk Istiarti; Syamsulhuda BM (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Handwashing with soap is the simplest way to prevent some infectious diseases such as diarrhea and hepatitis. Based on data from Health Profile in Purworejo District in 2015, it is known that the morbidity rate of diarrhea case in Banyuurip Public Health Center (PHC) is always higher than other PHCs in the same district. The purpose of this research is to analyze some factors related to practice of handwashing with soap in elementary schools, that are located in Banyuurip Public Health Center. This research is a quantitative study with descriptive analysis, using cross sectional approach. Samples of this research are 72 elementary school students located in Banyuurip Public Health Center, Purworejo. The result of this research showed that 68,1% of students practice handwashing with soap well and they used standardized tools, such as using flowing water, soap, towels or wipes, and they had done 7 steps of handwashing with soap. This study showed that 31,9% of students did not practice handwashing with soap well. Bivariate analysis showed that there are five variables related to handwashing with the soap i.e.: the knowledge about handwashing with soap (p-value = 0,019), attitude towards handwashing with soap (p-value = 0,009), teachers’ support (p-value = 0,005), peers’ support (p-value = 0,026), and availability of handwashing with soap facilities (p-value = 0.046). It is suggested to the relevant authorities to give health education about handwashing with soap in order to increase the knowledge and positive attitude among students toward handwashing with soap. The school is expected to complete some tools in supporting handwashing with soap at school. The teachers are expected to increase their support to students in practicing handwashing with soap, and they are also expected to guide students to give support each other to practice handwashing with soap well.